Polyisoprene Nanoparticles Prepared by Polymerization in Microemulsion. (17th August 2010) - Apolinar, Y.; Ramos, L. F.; Saade, H.; Díaz de León, R.; López, R. G.
Abstract : Batch polymerization of isoprene was carried out at25 ∘ C in a normal microemulsion stabilized with sodium dodecyl sulfate and initiated with the redox couple tert -butyl hydroperoxide/tetraethylene-pentamine. Characterization by transmission electronic microscopy showed that polyisoprene nanoparticles with number-average diameter close to 20 nm were obtained. The low molecular weights obtained, as determined by gel permeation chromatography, were probably due to chain scission as inferred from the oxidative ambient at which polymerization was carried out. Microstructure calculated from infrared spectroscopy data indicates that the obtained polyisoprene contains around 80% total 1, 4 units, which is in accordance with its glass transition temperature (- 60.8 ∘ C ) determined by differential scanning calorimetry.